Teachers' Efforts to Overcome Delays in Learning Arabic as an Impact of During Learning for Slow Learner Students in Junior High Schools - Hafiza, Rizka; Ahkas, Akmal Walad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The purpose of this study was to describe the teacher's efforts to overcome delays in learning Arabic as an impact of online learning for Slow Learner students at SMP IT Ad-Durrah Medan. This study used a qualitative approach with a case study type of research. Primary data were obtained from Arabic teachers. At the same time, secondary data was slow learner students and Arabic language textbooks for class VII SMP IT Ad-Durah Medan. The data collection techniques that the researchers used were observation, documentation, and interviews. After collecting the results in the field, the researcher will select and organize the data. Furthermore, the researcher classified the data, organized the data, selected the significance of the data, analyzed the data, and drew conclusions. The results of the study showed that efforts to overcome delays in learning Arabic for students at SMP IT Ad-Durrah Medan due to the impact of during learning which had been running for two years, are as follows: 1) Motivate Students who are slow to learn Arabic, 2) Developing Learning Strategies Towards Effective Arabic Learning, 3) Developing Materials about Things that Happen among Learners, 4) Using Learning Media, Applying Multimethods and Learning Strategies, 5) Evaluating Authentic. From the final results of learning Arabic, it was found that 97-99% of students were declared complete in Arabic lessons. In the odd semester of the 2022/2023 academic year, the results of learning Arabic were yet to be discovered because learning was still ongoing. However, based on the results achieved in previous years, the success rate of students' Arabic was very high.